Numerical investigation of drop formation in a co‐current liquid–liquid flow for ice slurry making system. Issue 3 (23rd May 2018) - Zhang, Tiantian; Xin, Yi; Geng, Fan; Han, Dongtai; Peng, Zhengbiao; Chai, Hongli; Luo, Gang; Ding, Haiyan
Abstract: Ice slurry is used widely as phase change materials (PCMs) to reduce the peak demand for power system. Drop formation plays a key role during ice slurry production in liquid–liquid circulating fluidized bed. In the present work, drop formation in a co‐current liquid–liquid flow was investigated via a 3D model. Volume of fluid method was adopted to study drop characteristics by tracking the interface. Major influences of the water velocity, the oil velocity, the jet size, and the jet number on drop formation were analyzed for drop characteristics. The results indicate that properties of drop formation vary significantly according to the different conditions. The drop size was distributed mainly as the normal distribution, and the average drop diameter varies with different conditions. The drop size varies from 0.7 to 1.9 mm at the water velocity of 0.5 m/s, whereas the size of drop size varies from 1.8 to about 2.65 mm at the water velocity of 1.5 m/s. Furthermore, the residence time of drop decreases obviously with the increase of the oil velocity. When the oil velocity is 0.1 m/s, a drop leaves the top outlet at about 0.44 s. When the oil velocity is 0.3 m/s, a drop reaches the outlet at about 0.15 s. Additionally, the simulated results were compared with the relevant experimental results and the previous simulated results. Reasonable agreements have been gained, which can validate the established model to some extent.